Mutual chemical effect of autograft and octacalcium phosphate implantation on enhancing intramembranous bone regeneration. Issue 1 (31st December 2021) - Ozaki, Hisashi; Hamai, Ryo; Shiwaku, Yukari; Sakai, Susumu; Tsuchiya, Kaori; Suzuki, Osamu
ABSTRACT: This study examined the effect of a mixture of octacalcium phosphate (OCP) and autologous bone on bone regeneration in rat calvaria critical-sized defect (CSD). Mechanically mixed OCP and autologous bone granules (OCP+Auto), approximately 500 to 1000 μm in diameter, and each individual material were implanted in rat CSD for 8 weeks, and subjected to X-ray micro-computed tomography (micro-CT), histology, tartrate-resistant acid phosphatase (TRAP) staining, and histomorphometry for bone regeneration. Osteoblastic differentiation from mesenchymal stem cells (D1 cells) was examined in the presence of non-contacting materials by alkaline phosphatase (ALP) activity for 21 days. The material properties and medium composition before and after the incubation were determined by selected area electron diffraction (SAED) under transmission electron microscopy (TEM), Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), and chemical analysis. The results showed that while bone formation coupled with TRAP-positive osteoclastic resorption and cellular ALP activity were the highest in the Auto group, a positive effect per OCP weight or per autologous bone weight on ALP activity was found. Although the OCP structure was maintained even after the incubation (SAED), micro-deposits were grown on OCP surfaces (TEM). Fibrous tissue was also exposed on the autologous bone surfaces (SEM). Through FT-IR absorption, it was determined that bone mineral-like characteristics of the phosphate group increased in the OCP + Auto group. These findings were interpreted as a structural change from OCP to the apatitic phase, a conclusion supported by the medium degree of saturation changes. The results demonstrate the mutual chemical effect of mixing OCP with autologous bone as an active bone substitute material. Graphical abstract: uf0001